2008
DOI: 10.1111/j.1558-5646.2007.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Experimental Alterations of the Operational Sex Ratio in Populations of Drosophila Melanogaster

Abstract: Theory predicts that males adapt to sperm competition by increasing their investment in testis mass to transfer larger ejaculates.Experimental and comparative data support this prediction. Nevertheless, the relative importance of sperm competition in testis size evolution remains elusive, because experiments vary only sperm competition whereas comparative approaches confound it with other variables, in particular male mating rate. We addressed the relative importance of sperm competition and male mating rate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 46 publications
1
80
0
Order By: Relevance
“…Our results highlight the importance of considering male mating rate as a selective pressure influencing testes size, in combination with sperm competition (see also [21]). The lack of a positive relationship between testis size and sperm number and the significant negative relationship between testis size and ejaculate volume also demonstrates that it is unsafe to assume that larger testes necessarily equate with more voluminous ejaculates and/or higher sperm counts.…”
Section: Discussionmentioning
confidence: 54%
“…Our results highlight the importance of considering male mating rate as a selective pressure influencing testes size, in combination with sperm competition (see also [21]). The lack of a positive relationship between testis size and sperm number and the significant negative relationship between testis size and ejaculate volume also demonstrates that it is unsafe to assume that larger testes necessarily equate with more voluminous ejaculates and/or higher sperm counts.…”
Section: Discussionmentioning
confidence: 54%
“…Experiments which manipulate the degree of polyandry have also been performed (e.g. Wigby & Chapman 2004;Crudgington et al 2005;Bacigalupe et al 2007;Linklater et al 2007;Reuter et al 2008;Hosken et al 2009). Together, these studies support the idea that experimental evolutionary manipulations of sexual selection and sexual conflict can lead to significant divergence in both pre-and post-mating traits.…”
Section: Introduction (A)mentioning
confidence: 56%
“…However, in another species of fruit fly, Drosophila melanogaster, which has less exaggerated sperm size, our prediction contradicts the results of an artificial-selection experiment. Reuter et al (2008) showed that more femalebiased conditions increased the level of sperm depletion and decreased the female remating rate. The reason for the discrepancy could be ascribed to our model's assumption that females obtain all sperm before beginning oviposition; however, the females of D. melanogaster can recover their fertility by additional matings after they are depleted of sperm (Bloch Qazi and Hogdal 2010).…”
Section: Implications For Empirical Studiesmentioning
confidence: 98%